2022
DOI: 10.1161/strokeaha.121.037581
|View full text |Cite
|
Sign up to set email alerts
|

Epitranscriptome in Ischemic Cardiovascular Disease: Potential Target for Therapies

Abstract: The global risk of cardiovascular disease, including ischemic disease such as stroke, remains high, and cardiovascular disease is the cause of one-third of all deaths worldwide. The main subjacent cause, atherosclerosis, is not fully understood. To improve early diagnosis and therapeutic strategies, it is crucial to unveil the key molecular mechanisms that lead to atherosclerosis development. The field of epitranscriptomics is blossoming and quickly advancing in fields like cancer research, nevertheless, poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 102 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…m 6 A is a type of dynamic and reversible RNA modification that plays critical roles in gene expression regulation 29 and mRNA stability 30 and homeostasis 31 . RNA modification is involved in disease development and can be used in the clinic 32 . However, the role of RNA modification in BP regulation is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…m 6 A is a type of dynamic and reversible RNA modification that plays critical roles in gene expression regulation 29 and mRNA stability 30 and homeostasis 31 . RNA modification is involved in disease development and can be used in the clinic 32 . However, the role of RNA modification in BP regulation is unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 31 RNA modification is involved in disease development and can be used in the clinic. 32 However, the role of RNA modification in BP regulation is unknown. In the present study, we showed that searching for RNAm‐SNPs in genomic loci was essential for a better understanding of GWAS signals.…”
Section: Discussionmentioning
confidence: 99%
“…When stimulated by lipopolysaccharides, YTHDF2-deficient macrophages can activate the MAPK and NF-κB signaling pathways and enhance the expression levels of signaling molecules, particularly TNF-α, IL-1β, IL-6, and IL-12 ( Yu et al, 2019 ). METTL3-deficient macrophages suppress oxLDL-induced m6A levels and inflammatory responses ( Quiles-Jiménez et al, 2022 ). m6A regulators also play a critical role in macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%